Teachers Feedback in Teaching Writing of Narrative Texts to the Eight Grade Students - Yuni Ansari Rambe; Anni Holila Pulungan; Syahron Lubis (LINGUISTIK TERAPAN, 2020)
Writing skills is considered the most difficult skill. The students usually face many difficulties in exploring the ideas or even finding the appropriate words to what they want to write. In this research, the researcher focuses on giving teachers written feedback in teaching writing narrative texts to the eight graders of SMP Amiruddiniyah Rantau Prapat. Written feedback is taken to provide an interaction between students writing and the teacher. In this process a teacher read the students work and responds to it through some written comments. The subjects of the study were the students of Eight grades. There were forty students, twenty male and twenty female students. This study is descriptive qualitative. The instruments that are used by the researcher are observation checklist, field notes, and students written works. the researcher collected the data from three observations. The first observation, the writing task was given to check the understanding of the students in writing narrative text,but the teacher did not give feedback. In the second and third observations feedback were given. In the second observation, the writing task was done in groups. Meanwhile in the third observation, it was done individually. The researcher analyzed the students written works that had been given written feedback from the teacherKeywords: Teacher Written Feedback, Writing, Narrative text, Students Written Work